Cell-free DNA hypermethylated genes may have a limited role in cancer screening but a potential role in risk assessment of head and neck cancer. (November 2022) - Liu, Wei; Ji, Tong; Zhang, Chenping; Zhou, Qin; Bao, Zhexuan
Abstract: Cell-free DNA (cfDNA) hypermethylation in blood-based liquid biopsy is an attractive, minimally invasive biomarker for head and neck cancer (HNC) diagnosis and risk assessment. Yet, there is a lack of adequate description and discussion on this issue. A total of 10 eligible case-control studies containing 26 different hypermethylated genes in cfDNA were retrieved. There were 2026 HNC patients and 3149 healthy individuals for determining various hypermethylated genes in cfDNA. The pooled diagnostic parameter of sensitivity, specificity, and diagnostic accuracy value (95% confidence interval) was 33.2% (31.2–35.3%), 93.3% (92.3–94.1%), and 69.8% (68.5–71.0%), respectively. Odds ratios analysis revealed that SHOX2, SEPT, HIC1, CDKN2A, and CALML5 were significantly associated with increased risk of HNC development. Collectively, cfDNA hypermethylation biomarkers had a high specificity but accompanied by a low sensitivity for HNC detection, which might have a limited role in cancer screening but a potential role in risk assessment of HNC.